2006
DOI: 10.7326/0003-4819-144-2-200601170-00006
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin-Resistant Genotypes and Eradication of Helicobacter pylori

Abstract: The A2143G mutation seemed to be associated with a very low eradication rate. The sequential regimen achieved a higher cure rate than standard therapy even in patients with these strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
147
3
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(170 citation statements)
references
References 35 publications
11
147
3
2
Order By: Relevance
“…Previous studies have suggested that the presence of the A2143G mutation confers a significantly decreased H. pylori eradication potential when using clarithromycin-containing regimens, more so than the presence of the A2142C or A2142G mutations. 24 At this time, the clinical manifestations and current therapies for each are identical and there is no utility for differentiation between the strains in the clinical laboratory setting. However, differentiation of mutations may have importance in future epidemiological studies or as recommendations for antimicrobial therapies change.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the presence of the A2143G mutation confers a significantly decreased H. pylori eradication potential when using clarithromycin-containing regimens, more so than the presence of the A2142C or A2142G mutations. 24 At this time, the clinical manifestations and current therapies for each are identical and there is no utility for differentiation between the strains in the clinical laboratory setting. However, differentiation of mutations may have importance in future epidemiological studies or as recommendations for antimicrobial therapies change.…”
Section: Discussionmentioning
confidence: 99%
“…The T2183C and A2223G mutations have been frequently found to be the cause of observed CAM resistance, while the A2143G mutation, which has a much stronger impact than the A2142G and A2142C [18]. mutations responsible for 90% of primary CAM-resistant H. pylori cases isolated in Western countries [19], accounted only for 23% of resistant strains in Asia [19].…”
Section: Discussionmentioning
confidence: 99%
“…This regimen includes a PPI and amoxicillin for 5 d, followed by a PPI, clarithromycin, and tinidazole triple therapy for another 5 d. Several studies have indicated that the eradication rate of sequential therapy was significantly higher than that of STT [85][86][87] . The reason that sequential therapy has a higher eradication rate than STT is that amoxicillin and PPI administered during the first 5 d decreases H. pylori density in the stomach, which increases clarithromycin and metronidazole efficacy [32,[88][89][90] . In addition, amoxicillin damages the bacterial cell wall and limits production of an efflux channel underlying drug resistance.…”
Section: Are There Suitable Sequential and Concomitant Therapy Alternmentioning
confidence: 99%
“…Clarithromycin resistance is due to three point mutations at A2142C, A2142G, and A2143G in the 23s rRNA gene [31] . In particular, the A2143G mutation has been related to a very low eradication rate [32] . In contrast, the A2143G mutation occurs in only 23% of resistant strains in Eastern countries [31] .…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 99%